Case report: Concomitant EGFR mutation and ALK rearrangement in non-small cell lung cancer - Haoyue Hu; Songtao Tan; Songtao Tan; Meng Xie; Peng Guo; Qiang Yu; Qiang Yu; Juan Xiao; Kangrui Zhao; Qiong Liao; Yi Wang (Frontiers Media S.A., 2023)
In non-small cell lung cancer (NSCLC), two key genetic alterations, epidermal growth factor receptor (EGFR) mutations and anaplastic lymphoma kinase (ALK) rearrangements, are commonly believed to be mutually exclusive. Studies have reported that concurrent EGFR/ALK co-mutation in non-small cell lung cancer patients is rare, with a prevalence ranging from 0.1% to 1.6%. However, the clinical and pathological characteristics of these patients are not well-defined, and the optimal treatment approach for such cases remains controversial. In this report, we present a case of stage IV lung adenocarcinoma with both epidermal growth factor receptor and anaplastic lymphoma kinase mutations, along with high PD-L1 expression. The patient initially received treatment with epidermal growth factor receptor tyrosine kinase inhibitors (TKIs), but the disease progressed. However, following a switch to ALK-TKI therapy and local radiotherapy, the lesion showed regression. Our report also provides a comprehensive summary of the clinical and pathological features, as well as treatment strategies, for non-small cell lung cancer patients with concurrent epidermal growth factor receptor mutation and anaplastic lymphoma kinase rearrangement.